Conceptualizing the water sensitive home in Sweden - Mangold, M.; Morrison, Gregory (2012)
We define the water sensitive home by assigning attributes to relevant aspects of water in the home. The intention of this study is to look at more physical attributes and leaving the social dimensions to later, more applied studies. Fig. 1 below illustrates the attributes. Table 1 gives the unit and indicator used for assessing each attribute. We build upon the work done by Hellström et al. (2004), Lundin and Morrison (2002) when we define attributes. The attributes are grouped depending on their mathematical nature, environmental loads are negative per definition, risks cannot be completely avoided, resource consumption should be limited but is needed and thus have an optimal level, likewise is accessibility regulated by authorities. In different contexts the optimal levels are different, the "sides" of the green building in fig. 1, depending on regulations. Furthermore a minimal, or human right, level has been identified based on WHO (2011).